2016
DOI: 10.18671/scifor.v44n111.07
|View full text |Cite
|
Sign up to set email alerts
|

Influence of genetic material and radial position on the anatomical structure and basic density of wood from Eucalyptus spp. and Corymbia citriodora

Abstract: O objetivo deste trabalho foi avaliar o efeito do material genético e da variabilidade radial na estrutura anatômica e densidade básica das madeiras de Eucalyptus sp. e Corymbia citriodora e também verificar a influência da anatomia sobre a densidade básica da madeira. Foram estudados dois híbridos naturais de Eucalyptus urophylla e a espécie Corymbia citriodora, sendo três árvores amostradas por material genético, e todos os plantios localizados no estado de Minas Gerais, Brasil. Retiraram-se nove discos (um … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
3
0
2
Order By: Relevance
“…This difference is due to changes in the meristem and the mechanical and physiological requirements of the tree development process, represented by increased fiber wall thickness and reduced vessel frequency and diameter, as the mature wood is formed in the trunk of E. grandis and E. grandis × urophylla trees 19,34 . The density increase over time is due to the xylem production with thin cell exchange, called juvenile wood, during the beginning of the secondary growth with more robust cells produced, forming the mature wood 35 .…”
Section: Discussionmentioning
confidence: 99%
“…This difference is due to changes in the meristem and the mechanical and physiological requirements of the tree development process, represented by increased fiber wall thickness and reduced vessel frequency and diameter, as the mature wood is formed in the trunk of E. grandis and E. grandis × urophylla trees 19,34 . The density increase over time is due to the xylem production with thin cell exchange, called juvenile wood, during the beginning of the secondary growth with more robust cells produced, forming the mature wood 35 .…”
Section: Discussionmentioning
confidence: 99%
“…A similar variation pattern for FL was also recently described by Palermo et al (2015) to determine the limits between adult and juvenile wood of Eucalyptus grandis wood, and for increasing behavior of BD by Hein et al (2015) who studied the effect of terrain slope and wind velocity on the BD and other Eucalyptus grandis hybrids × E.urophylla wood properties. Melo et al (2016) also observed a significant radial increase in fiber length and basic density in Eucalyptus spp. and Corymbia citriodora woods.…”
Section: Variation Of the Wood Properties In The Pith-bark Directionmentioning
confidence: 61%
“…Outros trabalhos da literatura avaliaram as correlações demonstradas na Tabela 7. MELO et al [3] encontraram correlação negativa entre a densidade básica e a frequência dos vasos e correlação positiva entre a espessura das paredes das fibras com a densidade em amostras de Eucalyptus. Essa correlação negativa entre a densidade e a frequência dos vasos também foi observada por TOMAZELLO FILHO [4].…”
Section: Resultsunclassified
“…A sua anatomia descreve o arranjo dos elementos celulares do lenho das árvores. A variação das dimensões dos elementos anatômicos interfere na qualidade da madeira, uma vez que a dimensão, distribuição e o arranjo estrutural das células propiciam as propriedades de resistência mecânica, a trabalhabilidade e os isolamentos térmico e acústico [2][3][4][5][6].…”
Section: Introductionunclassified